2011
DOI: 10.1161/strokeaha.110.594754
|View full text |Cite
|
Sign up to set email alerts
|

Wide Variation in Definition, Detection, and Description of Lacunar Lesions on Imaging

Abstract: Background and Purpose-Variation in the definition of lacunar lesions on imaging and difficulties in their detection may be hampering lacunar stroke research. We assessed literature definitions of imaging lacunar lesions and the definitions and detection of lacunar lesions among small-vessel disease researchers. Methods-We assessed definitions of imaging lacunar lesion in 50 randomly selected articles from 3 stroke-related journals and an online survey of small-vessel disease researchers. In the literature rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 31 publications
1
75
4
2
Order By: Relevance
“…With regard to defining SBI, inconsistent radiological criteria for diagnosing infarction have been applied. Consequently, prevalence is underestimated by definitions limiting SBIs to lacunes or lesions with cerebrospinal fluid (CSF)-like signal intensity (reflecting only completed and cavitated infarcts) in light of evidence that 30% to 80% of lacunes do not cavitate [62,63]. Conversely, more inclusive signal definitions, including lesions ≤3 mm in diameter overestimate prevalence.…”
Section: Limitationsmentioning
confidence: 99%
“…With regard to defining SBI, inconsistent radiological criteria for diagnosing infarction have been applied. Consequently, prevalence is underestimated by definitions limiting SBIs to lacunes or lesions with cerebrospinal fluid (CSF)-like signal intensity (reflecting only completed and cavitated infarcts) in light of evidence that 30% to 80% of lacunes do not cavitate [62,63]. Conversely, more inclusive signal definitions, including lesions ≤3 mm in diameter overestimate prevalence.…”
Section: Limitationsmentioning
confidence: 99%
“…A 30-day DWI limit was applied, because this represents an accepted time for DWI to remain sensitive for infarct detection in patients with acute ischemic stroke. 11,17 LI was defined as solitary, subcortical lesions, Յ20 mm in greatest diameter as previously defined, 15 recommended, 18 and clinically applied. 19,20 The final study cohort comprised 88 patients.…”
Section: Study Cohortmentioning
confidence: 99%
“…In USA, several studies have examined the difference in frequency of ischemic stroke subtypes by race. Blacks are more prone to small vessel stroke than Whites 18 . LACI accounts for 20 to 25% of all ischemic strokes [19][20][21] , and this proportion is the highest in the African Americans than in the white population 22,23 .…”
mentioning
confidence: 94%
“…This was most often found in the parietal lobe (73.6%) for Obajimi et al Potter et al 18 and Bailey et al 28 found lesions occurring more often in the internal capsule and caudate nucleus.…”
mentioning
confidence: 95%